2012
DOI: 10.3945/jn.112.157578
|View full text |Cite
|
Sign up to set email alerts
|

Maize Porridge Enriched with a Micronutrient Powder Containing Low-Dose Iron as NaFeEDTA but Not Amaranth Grain Flour Reduces Anemia and Iron Deficiency in Kenyan Preschool Children

Abstract: Few studies have evaluated the impact of fortification with iron-rich foods such as amaranth grain and multi-micronutrient powder (MNP) containing low doses of highly bioavailable iron to control iron deficiency anemia (IDA) in children. We assessed the efficacy of maize porridge enriched with amaranth grain or MNP to reduce IDA in Kenyan preschool children. In a 16-wk intervention trial, children (n = 279; 12-59 mo) were randomly assigned to: unrefined maize porridge (control; 4.1 mg of iron/meal; phytate:iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…In-home iron fortification, where the caregiver adds vitamins and minerals to weaning foods at home using micronutrient powders (MNPs) containing iron reduces IDA risk in African infants, even in areas with high prevalence of infection and inflammation [12,13,14,15]. The most widely-used MNP is the “Sprinkles” formulation; it provides a high dose of 12.5 mg iron/day in order to deliver adequate absorbed iron even when added to complementary foods rich in inhibitors of iron absorption.…”
Section: Iron-containing Micronutrient Powdersmentioning
confidence: 99%
“…In-home iron fortification, where the caregiver adds vitamins and minerals to weaning foods at home using micronutrient powders (MNPs) containing iron reduces IDA risk in African infants, even in areas with high prevalence of infection and inflammation [12,13,14,15]. The most widely-used MNP is the “Sprinkles” formulation; it provides a high dose of 12.5 mg iron/day in order to deliver adequate absorbed iron even when added to complementary foods rich in inhibitors of iron absorption.…”
Section: Iron-containing Micronutrient Powdersmentioning
confidence: 99%
“…In the MixMe MNP, NaFeEDTA is combined with ascorbic acid and an exogenous phytase, both of which are enhancers of iron absorption, and this combination results in higher iron absorption from maize porridge (16). This MNP has shown to have weak efficacy in preschool children in Kenya (19) and school-age children in South Africa (20); however, in a 1-y controlled trial in Kenyan infants, the MNP did not reduce IDA (21), possibly because the absorbed iron dose was insufficient as a result of the low dose and the high prevalence of infections increasing serum hepcidin (12). Thus, it is uncertain how far the iron dose in MNPs can be lowered while maintaining efficacy against anemia.…”
mentioning
confidence: 99%
“…The choice of processed food vehicles varies widely by region and context, depending on the subpopulation targeted, food consumption and acceptability, food availability and sustainability, as well as the financial and technical concerns. The staple food is the most commonly used as vehicle of fortification, in addition, milk powder, beverages, biscuits, the most commonly used sauce, such as soy sauce, drink and water, can also be used as fortified foods [92][93][94][95][96][97][98][99][100][101][102][103][104].…”
Section: Food Fortification With Ironmentioning
confidence: 99%
“…A nutrition intervention trial conducted in India showed that iron-fortified biscuits led to a significant enhancement in haemoglobin status of anaemic school children in rural areas [98]. Another study showed that maize porridge fortified with multi-micronutrient powder contained low dose, highly bioavailable iron can reduce the prevalence of IDA in pre-school children [102]. Home fortification with multi-micronutrient powder with low dosages of bioavailable iron may therefore be a promising strategy to improve iron status among children.…”
Section: Food Fortification With Ironmentioning
confidence: 99%